Implementing the SNIS recommendations for neurointerventional emergent care in the setting of COVID-19: impact on stroke metrics and patient outcomes. (23rd March 2021) - Atchie, Benjamin; Jarvis, Stephanie; Stoddard, Erica; Salottolo, Kristin; Nieberlein, Amy; McCarthy, Kathryn; Bartt, Russell; Bennett, Alicia; Burrell, Christian; Frei, Donald; Bar-Or, David
Abstract : Background: It is not clear whether the COVID-19 pandemic and subsequent Society of Neurointerventional Surgery (SNIS) recommendations affected hospital stroke metrics. Methods: This retrospective cohort study compared stroke patients admitted to a comprehensive stroke center during the COVID-19 pandemic April 1 2020 to June 30 2020 (COVID-19) to patients admitted April 1 2019 to June 30 2019. We examined stroke admission volume and acute stroke treatment use. Results: There were 637 stroke admissions, 52% in 2019 and 48% during COVID-19, with similar median admissions per day (4 vs 3, P=0.21). The proportion of admissions by stroke type was comparable (ischemic, P=0.69; hemorrhagic, P=0.39; transient ischemic stroke, P=0.10). Acute stroke treatment was similar in 2019 to COVID-19: tPA prior to arrival (18% vs, 18%, P=0.89), tPA treatment on arrival (6% vs 7%, P=0.85), and endovascular therapy (endovascular therapy (ET), 22% vs 25%, P=0.54). The door to needle time was also similar, P=0.12, however, the median time from arrival to groin puncture was significantly longer during COVID-19 (38 vs 43 min, P=0.002). A significantly higher proportion of patients receiving ET were intubated during COVID-19 due to SNIS guideline implementation (45% vs 96%, P<0.0001). There were no differences by study period in discharge mRS, P=0.84 or TICI score, P=0.26. Conclusions: The COVID-19 pandemic did not significantly affect stroke admission volume or acute stroke treatment utilization. Outcomes were not affected by implementing SNIS guidelines. Although there was a statistical increase in time to groin puncture for ET, it was not clinically meaningful. These results suggest hospitals managing patients efficiently can implement practices in response to COVID-19 without impacting outcomes.